Successful remote delivery of a treatment for phonological alexia via telerehab. Issue 4 (3rd July 2016) - Getz, Heidi; Snider, Sarah; Brennan, David; Friedman, Rhonda
Abstract : A growing body of literature supports the effectiveness of the remote delivery of rehabilitation services, i.e., telerehab. Aphasia treatment is particularly well suited for telerehab because of the verbal and visual nature of speech-language therapy, but scientific research investigating aphasia telerehab is in its infancy. No studies to date have evaluated whether treatment of acquired reading disorders by a live clinician can be feasibly, effectively, or efficiently conducted via telerehab. Here we address this gap in the literature by reporting our success remotely remediating the reading deficits of two participants with phonological alexia. We adapted for the telerehab setting a previously validated treatment for phonological alexia (Friedman, Sample, & Lott, 2002 ), which uses a paired-associate design to train reading of problematic words. Both telerehab participants significantly improved their reading of trained words in similar time frames as previous participants (Friedman et al., 2002 ; Kurland et al., 2008 ; Lott, Sample, Oliver, Lacey, & Friedman, 2008 ); furthermore, both participants reported high satisfaction with the telerehab setting. Although telerehab with alexic patients poses unique challenges, we conclude that treatment for alexia via telerehab is nevertheless feasible, may be equally effective as in-person treatment, and saves substantial resources for participants as well as clinicians.